Molecular Mapping of Reduced Plant Height Gene Rht24 in Bread Wheat - Tian, Xiuling; Wen, Weie; Xie, Li; Fu, Luping; Xu, Dengan; Fu, Chao; Wang, Desen; Chen, Xinmin; Xia, Xianchun; Chen, Quanjia; He, Zhonghu; Cao, Shuanghe (Frontiers in Plant Science, 2017)
Height is an important trait related to plant architecture and yield potential in bread wheat (Triticum aestivum L.). We previously identified a major quantitative trait locus (QTL) QPH.caas-6A flanked by simple sequence repeat markers Xbarc103 and Xwmc256 that reduced height by 8.0–10.4%. Here QPH.caas-6A, designated as Rht24, was confirmed using recombinant inbred lines (RILs) derived from a Jingdong 8/Aikang 58 cross. The target sequences of Xbarc103 and Xwmc256 were used as queries to BLAST against International Wheat Genome Sequence Consortium database and hit a super scaffold of approximately 208 Mb. Based on gene annotation of the scaffold, three gene-specific markers were developed to genotype the RILs, and Rht24 was narrowed to a 1.85 cM interval between TaAP2 and TaFAR. In addition, three single nucleotide polymorphism (SNP) markers linked to Rht24 were identified from SNP chip-based screening in combination with bulked segregant analysis. The allelic efficacy of Rht24 was validated in 242 elite wheat varieties using TaAP2 and TaFAR markers. These showed a significant association between genotypes and plant height. Rht24 reduced plant height by an average of 6.0–7.9 cm across environments and were significantly associated with an increased TGW of 2.0–3.4 g. The findings indicate that Rht24 is a common dwarfing gene in wheat breeding, and TaAP2 and TaFAR can be used for marker-assisted selection.